Secret coders - Yang, Gene Luen; Holmes, Mike (Comic book artist) (New York : :01, First Second Books, 2015)
"Welcome to Stately Academy, a school which is just crawling with mysteries to be solved! The founder of the school left many clues and puzzles to challenge his enterprising students. Using their wits and their growing prowess with coding, Hopper and her friend Eni are going to solve the mystery of Stately Academy no matter what it takes!" --
"Get with the program!"--Cover.
Chiefly illustrations.
Middle School.
Accelerated Reader
380
Keywords: Gifted children -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Computer programming -- Comic books, strips, etc; Graphic novels